2016
DOI: 10.1089/thy.2015.0376
|View full text |Cite
|
Sign up to set email alerts
|

Bethesda Categorization of Thyroid Nodule Cytology and Prediction of Thyroid Cancer Type and Prognosis

Abstract: In addition to predicting cancer prevalence, the TBS also imparts important prognostic information about cancer type, variant, and risk of recurrence. These data extend the utility of TBS classification by fostering an improved understanding of the risk posed by any confirmed malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
62
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 26 publications
2
62
0
2
Order By: Relevance
“…Our findings are consistent with those reported by Lastra et al who found that of the malignant tumors resected at their institution with a suspicious Afirma result and a preceding AUS/FLUS or SFN diagnosis, 73% were FVPTCs (the FVPTCs were not further subclassified in this study), 14% were classical PTCs, and 14% were FTCs (24). Moreover, the finding that many of the carcinomas detected by the GEC are NFVPTCs is a direct reflection of the fact that the Bethesda categorization of a nodule is associated with tumor type, stage, and prognosis (22,25). In other words, carcinomas resected in the setting of an AUS/FLUS or SFN FNA diagnosis are usually FVPTCs without associated extrathyroidal extension or lymph node metastases (22,25).…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Our findings are consistent with those reported by Lastra et al who found that of the malignant tumors resected at their institution with a suspicious Afirma result and a preceding AUS/FLUS or SFN diagnosis, 73% were FVPTCs (the FVPTCs were not further subclassified in this study), 14% were classical PTCs, and 14% were FTCs (24). Moreover, the finding that many of the carcinomas detected by the GEC are NFVPTCs is a direct reflection of the fact that the Bethesda categorization of a nodule is associated with tumor type, stage, and prognosis (22,25). In other words, carcinomas resected in the setting of an AUS/FLUS or SFN FNA diagnosis are usually FVPTCs without associated extrathyroidal extension or lymph node metastases (22,25).…”
Section: Discussionmentioning
confidence: 79%
“…Moreover, the finding that many of the carcinomas detected by the GEC are NFVPTCs is a direct reflection of the fact that the Bethesda categorization of a nodule is associated with tumor type, stage, and prognosis (22,25). In other words, carcinomas resected in the setting of an AUS/FLUS or SFN FNA diagnosis are usually FVPTCs without associated extrathyroidal extension or lymph node metastases (22,25). Specifically, Vanderlaan et al found that FVPTCs accounted for 85% and 73% of the PTCs associated with an AUS/FLUS and SFN FNA diagnosis, respectively (22), and Liu et al showed AUS, SUS, and malignant FNA diagnoses were progressively associated with an increasing risk of extrathyroidal extension ( p < 0.001) and local lymph node metastases ( p < 0.001) (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Atypia of undetermined significance or follicular lesion of undetermined significance (AUS/FLUS), follicular neoplasm or suspicious for follicular neoplasm (FN/SFN), and suspicious of malignancy (SM) categories in the Bethesda classification may be considered indeterminate cytologies. These groups are representative of morphologically abnormal findings that are related to an increased risk of malignancy, though not enough to confirm a malignant lesion (5). Majority of the nodules with indeterminate cytology are surgically excised due to their malignancy potential, which confronts the patients with risks of morbidity and complications related to unnecessary surgeries (6).…”
Section: Introductionmentioning
confidence: 99%
“…It is well documented that FVPTC does not express the conventional nuclear features of PTC and may localize the cytological diagnosis in subcategories. This may be one of the causes resulting the higher malignancy rates in histology as reported in several reports (12,13).…”
Section: Discussionmentioning
confidence: 87%